Édito - Amandine Charvet; Mareike Boldt (Nantes Université, 2024)
This issue analyses the relations between public education policies and curricular proposals. We put the multiplicity of these relations and the ways in which they operate are at the heart of the questions raised in this issue, with the aim of providing a new framework for understanding the school system. Analyses of public action in the field of education rarely look at the content transmitted and how it is translated into curricular and pedagogical proposals. Yet we believe that this translation into curricula is a relevant way of understanding changes in schools and their social logic. By looking at curricula, we can gain a better understanding of the way in which a society intends to train the younger generations, and of the particular type of individual it is aiming to build. From a multi-disciplinary perspective (mainly history, sociology, education and politics), the goal is to understand these reconfigurations at different levels, of policies and actors, in order to grasp their social logic and their consequences for school and educational transformations.